2023
DOI: 10.1111/jan.15802
|View full text |Cite
|
Sign up to set email alerts
|

Experiences of nurses and midwives with disabilities: A scoping review

Abstract: AimTo identify the extent and type of evidence exploring the workplace experiences of nurses and midwives with disabilities.DesignScoping Review.Data SourcesFour electronic databases were systematically searched in February 2022 to identify studies discussing the experiences of nurses and midwives with disabilities, published between 2012 and 2022. Google Scholar and Theses Global were also searched.Review MethodsAll search results, irrespective of their format, were uploaded to Covidence to assist with the se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 55 publications
0
3
0
Order By: Relevance
“…While the crucial role of nurses in healthcare is well-acknowledged, there are several underexplored areas of nursing practice that are examined in this special issue. For example, the experiences of disabled nurses (Baker et al, 2023), nurse-led models of care (Bassah et al, 2023), and the impact of varying interferences on nurses' working memory (Hu et al, 2023). In a scoping review, Baker et al (2023) identified the varying workplace experiences of nurses and midwives with disabilities.…”
Section: Under S Tudied Nur S Ing Phenomenamentioning
confidence: 99%
See 2 more Smart Citations
“…While the crucial role of nurses in healthcare is well-acknowledged, there are several underexplored areas of nursing practice that are examined in this special issue. For example, the experiences of disabled nurses (Baker et al, 2023), nurse-led models of care (Bassah et al, 2023), and the impact of varying interferences on nurses' working memory (Hu et al, 2023). In a scoping review, Baker et al (2023) identified the varying workplace experiences of nurses and midwives with disabilities.…”
Section: Under S Tudied Nur S Ing Phenomenamentioning
confidence: 99%
“…For example, the experiences of disabled nurses (Baker et al, 2023), nurse-led models of care (Bassah et al, 2023), and the impact of varying interferences on nurses' working memory (Hu et al, 2023). In a scoping review, Baker et al (2023) identified the varying workplace experiences of nurses and midwives with disabilities. They illuminated that nurses and midwives can be greatly affected by disability and highlighted the importance of diversity, equity, accessibility and inclusion across the profession (Baker et al, 2023).AscopingreviewbyBassahetal.…”
Section: Under S Tudied Nur S Ing Phenomenamentioning
confidence: 99%
See 1 more Smart Citation